Metabolism and pharmacological activities of the natural health-benefiting compound diosmin. Issue 10 (23rd September 2020) - Zheng, Yizhou; Zhang, Rui; Shi, Weimei; Li, Linfu; Liu, Hai; Chen, Zhixi; Wu, Longhuo
Abstract : Diosmin is a famous natural flavonoid for treating chronic venous insufficiency and varicose veins. Abstract : Diosmin is a famous natural flavonoid for treating chronic venous insufficiency and varicose veins. Recently, extensive study has indicated that diosmin possesses diverse pharmacological activities, including anti-inflammation, anti-oxidation, anti-diabetes, anti-cancer, anti-microorganism, liver protection, neuro-protection, cardiovascular protection, renoprotection, and retinal protection activities. Due to its low water solubility, diosmin is dramatically limited in clinical application. Expectedly, many potential strategies have been developed for improving its pharmacokinetic values and bioavailability. This health-benefiting compound has been explored as the major component of Daflon and micronized purified flavonoid fraction (MPFF), which have been used in clinics to improve micro-circulation. However, no specific drug targets for diosmin are reported, although some potential factors have been involved in screening, such as P-glycoprotein (P-gp), IKKβ, acetylcholinesterase (AChE), and aldose reductase (AR). More investigations on the underlying mechanisms of diosmin in mediating cellular processes with high specificity is still needed.